Artificial intelligence and its adoption in financial services - Lopes da Costa, R.; Cruz, M.; Gonçalves, R.; Dias, Á.; Vinhas da Silva, Rui; Pereira, L. (International Journal of Services Operations and Informatics, 2022)
In the current business landscape, a key issue of concern is that of society's transition to the information age. It follows therefore that it is increasingly important to adapt business models and adopt systems that are effectively capable of handling data, using artificial intelligence (AI). The financial industry is one of the sectors of the economy that will face the challenges of this transition. This study aims to understand what the perceptions of AI are and its impact in the financial sector. Thus, descriptive statistics were used to understand financial professionals´ and AI experts' views on AI. It was possible to conclude that perceptions regarding the impact that AI may have on this industry are different when seen from an operational perspective as opposed to a strategic perspective. Additionally, the adoption of AI accrues benefits not only to the systems themselves, but also to the companies that are proprietors of innovative technologies.